2016
DOI: 10.1063/1.4960110
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive neural network backstepping control for a class of uncertain fractional-order chaotic systems with unknown backlash-like hysteresis

Abstract: In this paper, we consider the control problem of a class of uncertain fractionalorder chaotic systems preceded by unknown backlash-like hysteresis nonlinearities based on backstepping control algorithm. We model the hysteresis by using a differential equation. Based on the fractional Lyapunov stability criterion and the backstepping algorithm procedures, an adaptive neural network controller is driven. No knowledge of the upper bound of the disturbance and system uncertainty is required in our controller, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Based on dual radial basis function (RBF) NNs, an adaptive fractional sliding mode controller is proposed to enhance the performance of the system in [34]. In [35], an adaptive NN control scheme is given for a class of fractional order systems with nonlinearities and backlash-like hysteresis. For a class of uncertain fractional order nonlinear systems with external disturbance and input saturation, an adaptive NN backstepping control method based on the indirect Lyapunov method is designed in [36].…”
Section: Introductionmentioning
confidence: 99%
“…Based on dual radial basis function (RBF) NNs, an adaptive fractional sliding mode controller is proposed to enhance the performance of the system in [34]. In [35], an adaptive NN control scheme is given for a class of fractional order systems with nonlinearities and backlash-like hysteresis. For a class of uncertain fractional order nonlinear systems with external disturbance and input saturation, an adaptive NN backstepping control method based on the indirect Lyapunov method is designed in [36].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, it was treated as an area of pure theoretical mathematics. Yet, during the past two decades, it had been shown that many actual systems, ranging from life sciences and materials engineering to secret communication and control theory, can be well modeled by fractional-order differential equations [1][2][3][4][5][6][7][8][9][10][11][12]. An important advantage of a fractionalorder system, as distinguished from the integer-order one, is that it has memory.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been proven that a lot kinds of actual systems, ranging from life science and engineering to secret communication and system control, can be better modeled by using fractionalorder differential equations (FDE) [1][2][3][4][5][6][7][8][9][10]. The nonlinear system, which is described by FDE, has memory.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that hysteresis can be found in a great mount of physical systems or devices, for instance, biology optics, mechanical actuators, electromagnetism, and electronic circuits [6,[23][24][25][26]. Hysteresis can damage the control performance or even lead to the instability of the controlled system.…”
Section: Introductionmentioning
confidence: 99%